Making sense of the average concept through engagement in model-eliciting activities. Issue 8 (14th September 2021) - Shahbari, Juhaina Awawdeh; Tabach, Michal
Abstract : The modelling approach to teaching and learning mathematics emphasizes the usefulness of mathematics in the real-world. The aim of the current study is to examine whether engagement in modelling activities provides learners an opportunity to expand their knowledge of a specific concept – the average concept. Our data include recordings of four groups of prospective teachers as they worked on two model-eliciting tasks. Their working process was video-recorded and transcribed and their discourse was then analysed via the communicational framework. Specifically, we monitored changes in the participants' use of the word average . The findings indicate that the participants expanded their use of the word average by shifting from references to arithmetic mean and reasonable values to references to benchmark, weighted value and mid-value.